1991
DOI: 10.1017/s0021859600067046
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different rates of application of organic and nitrogen fertilizers in a rice-based cropping system

Abstract: SUMMARYThe effect on soil fertility and crop performance of different organic fertilizers; paddy straw (PS), farmyard manure (FYM), water hyacinth compost (WHC) and tank silt (TS), at different rates of application and in combination with N fertilizer, was studied in a rice-based cropping system on an acid lateritic soil at Kharagpur, India, during 1985/86. Organic manuring of wet-season rice (first crop) with 5 t PS/ha 10 days before transplanting and 10 t FYM or 10 t WHC/ha at transplanting increased grain y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
0
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 3 publications
3
46
0
1
Order By: Relevance
“…The potential of cow dung, poultry droppings, refuse compost and farmyard manure as suitable soil amendments in the tropics has been reported [1,2,3,4]. Application of organic materials as fertilizers provides growthregulating substances and improves the physical, chemical and microbial properties of the soil [5,6,7,8]. Sole use of organic manures to sustain cropping has, however, been reported inadequate, as they are required in rather large quantities to meet crops' nutrient requirements because of their relatively low nutrient content [9].…”
Section: Introductionmentioning
confidence: 99%
“…The potential of cow dung, poultry droppings, refuse compost and farmyard manure as suitable soil amendments in the tropics has been reported [1,2,3,4]. Application of organic materials as fertilizers provides growthregulating substances and improves the physical, chemical and microbial properties of the soil [5,6,7,8]. Sole use of organic manures to sustain cropping has, however, been reported inadequate, as they are required in rather large quantities to meet crops' nutrient requirements because of their relatively low nutrient content [9].…”
Section: Introductionmentioning
confidence: 99%
“…The need to use renewable forms of energy has revived the use of organic fertilizers worldwide. Nutrients contained in organic manures are released more slowly and are stored for a longer time in the soil, thereby ensuring a long residual effect [2], supporting better root development, leading to higher crop yields [3].Improvement of environmental conditions and public health as well as the need to reduce costs of fertilizing crops are also important reasons for advocating increased use of organic materials [4].The soil fertility status is improved by activating the soil microbial biomass [5].To meet crops' nutrient supply, organic fertilizers are, however, required in rather large quantities. Application of organic manures sustains cropping systems through better nutrient recycling [6].Application of organic manures plays a direct role in plant growth as a source of all necessary macro and micronutrients in available forms during mineralization, thereby improving both the physical and the biological properties of the soil [7].Organic manures decompose to give humus which plays an important role in the chemical behaviour of several metals in soils through the flavonic and humic acid contents, which have the ability to retain the metals in complex and chelate forms [7].Organic manures also improve the water holding capacity of the soil; improve the soil structure and the soil aeration [5].The benefits derivable from the use of organic materials have however not been fully utilized in the humid tropics.…”
Section: Introductionmentioning
confidence: 99%
“…This is corroborated by Rousk et al [68] who reported that a higher pH value had a positive effect on the bacterial diversity and diverse effects on the abundance. In addition, nutrients in organic manures are not only released more slowly but they also persist in the soil for a longer period and for this reason ensure a longer residual effect compared to non-organic fertilizers [69,70].…”
Section: Effects Of N Fertilizer Type On N and C Cyclingmentioning
confidence: 99%